Acquired amegakaryocytic thrombocytopenia after durvalumab administration - Suyama, Takahiro; Hagihara, Masao; Kubota, Naoto; Osamura, Yoshiyuki; Shinka, Yoko; Miyao, Naoki (Journal of Clinical and Experimental Hematopathology, 2021)
Immune checkpoint inhibitors (ICIs), despite their ability to potentiate antitumor T-cell responses, may cause various immune-related adverse events. Most cases of thrombocytopenia induced by ICIs have revealed a pathophysiologic mechanism of immune thrombocytopenia with increased platelet destruction and preserved megakaryocytes. Acquired amegakaryocytic thrombocytopenic purpura (AATP) is an unusual disorder characterized by thrombocytopenia with markedly diminished bone marrow megakaryocytes in the presence of otherwise normal hematopoiesis. AATP caused by ICIs has not been reported on. Herein, we present the case of a 79-year-old man diagnosed with squamous cell carcinoma of the lung who developed AATP after two courses of durvalumab, a drug targeting programmed death-ligand 1. Two weeks after the second cycle, his platelet count decreased to 2.1 × 104/μL. After the patient underwent platelet transfusion, his platelet count increased to 8.1 × 104/μL the next day but subsequently decreased repeatedly even after the ICI was discontinued. Six weeks after the second cycle, he developed interstitial pneumonia and was administered prednisolone (50 mg/day). However, thrombocytopenia did not improve. Bone marrow biopsy showed scarce megakaryocytes (< 1 megakaryocyte/10 high-power fields) with preservation of myeloid and erythroid series. Myelodysplasia, myelofibrosis, or metastatic lesions were not observed. Cytogenetic analysis showed a normal male karyotype of 46XY. Hence, the patient received eltrombopag, a thrombopoietin receptor agonist, and his platelet count subsequently improved. After recovery, bone marrow aspiration revealed a normal number of megakaryocytes. AATP is rarely the type of thrombocytopenia induced by ICIs and may be successfully treated with thrombopoietin receptor agonists.